Optimization for Degradation of Antibiotics by Peroxyacetic Acid - Blouin, Mittal; Farnood, Fatih; Ozkan, Pooya; Leuschner, Schott; Eduardo, James (Journal of Functional Materials and Applied Engineering, 2024)
Antibiotics are typical emerging micro-pollutants in the aquatic environment, characterized by persistence, high risk, potential unknown toxicity, and widespread residue. AOPs that exploit ·OH, O₂·⁻ and SO₄·⁻ have become a hot research topic for antibiotic wastewater because they are fast, versatile and highly efficient. Starting from the structural characteristics of antibiotics and combining density functional theory (DFT), this study systematically analyzes, for the first time, the attack sites and degradation mechanisms of different reactive species on five common categories of antibiotics. Zero-valent iron (Fe⁰) was modified using the common aminopolycarboxylic acid (APCA) chelator EDTA via a liquid-phase impregnation method to construct an EDTA-Fe⁰/Peroxyacetic Acid (PAA) catalytic system. Using the typical antibiotic sulfamethazine (SMT) as the target pollutant, this paper investigates the influence of modification parameters, system dosage, initial pH, and coexisting anions, aiming to reveal the enhanced activation mechanism of EDTA-Fe⁰ within the system.